Reducing Error, Fraud and Corruption (EFC) in Social Protection Programs - Tesliuc, Emil Daniel; Milazzo, Annamaria (World Bank, Washington, DC, 2012)
Social Protection (SP) and Social Safety Net (SSN) programs channel a large amount of public resources, it is important to make sure that these reach the intended beneficiaries. Error, fraud, or corruption (EFC) reduces the economic efficiency of these interventions by decreasing the amount of money that goes to the intended beneficiaries, and erodes the political support for the program. While no program is immune to EFC, evidence from developed countries demonstrates that such leakage can be brought to negligible levels. In five Organization for Economic Co-operation and Development (OECD) countries (UK, Canada, Ireland, New Zealand, and USA) this fraction is between 2-5 percent for the SP sector as a whole. For SSN programs, which use more complex eligibility criteria and hence are more prone to EFC, this fraction is 10 percent. To achieve these results, programs have implemented a number of measures reviewed in this note. In contrast, efforts to combat or even measure EFC are quite rare in developing countries, although some programs are plagued by it.